Composition for thick film resistor, paste for thick film resistor, and thick film resistor

By using lead-free glass melting agent, osmium compound and graphite quartz stone in the thick film resistor composition, the current noise problem of high-impedance thick film resistors without lead is solved, and a balance between high impedance and low current noise is achieved.

JP7647811B2Active Publication Date: 2025-03-18SUMITOMO METAL MINING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023132876
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-03-18
Estimated Expiration
2039-06-05

AI Technical Summary

Technical Problem

In the prior art, high-impedance thick film resistors have no lead, current noise will increase, making it difficult to achieve both high impedance and low current noise.

Method used

A thick film resistor composition is used, which comprises a lead-free glass melting agent, an osmium compound as a conductive powder, and graphite quartz (Steatite) is added therein to adjust the resistance value and reduce the current noise.

Benefits of technology

The manufacturing of high-impedance thick film resistors is realized, without harmful lead, and has low current noise and good electrical characteristics, which can replace traditional lead-containing thick film resistors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647811000001
    Figure 0007647811000001
  • Figure 0007647811000002
    Figure 0007647811000002
Patent Text Reader

Abstract

To provide a thick film resistor that substantially does not contain lead while having a desired resistance value and good electrical characteristics such as low current noise.SOLUTION: In a thick film resistor composition, a thick film resistor paste, and a thick film resistor, a conductive component contains at least one selected from ruthenium dioxide, calcium ruthenate, strontium ruthenate, and barium ruthenate, and a glass component is substantially free of lead and contains steatite of 3.0 mass% or more and 15.0 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for forming thick film resistors in resistive components such as chip resistors and hybrid ICs. A thick-film resistor composition and a thick-film resistor paste used in the above-mentioned The present invention relates to a thick film resistor formed by [Background technology]

[0002] Conventionally, as a resistive component among electronic components, a thick film resistor formed using a resistive paste has been used. and thin film resistors formed by sputtering a film-forming material. Among these, thick film resistors are popular because the manufacturing equipment is inexpensive and the productivity is high. They are widely used as resistive components in devices such as trip resistors and hybrid ICs.

[0003] Thick film resistors are made by printing thick film resistor paste on a ceramic substrate and firing it. This paste for thick film resistors is made of conductive powder, glass frit, and and an organic vehicle for turning the ink into a paste suitable for printing.

[0004] Conductive powders include ruthenium dioxide (RuO2) and pyrochlore-type ruthenium oxide. Compound (Pb2Ru2O 7-X Ruthenium (Ru) compounds such as Bi2Ru2O7 Ruthenium compounds are commonly used as conductive powders mainly because This is because the resistance has the characteristic of changing gradually with respect to the change in concentration.

[0005] Glass frits include lead borosilicate glass (PbO-SiO2-B2O3) and aluminum. Lead-containing glass such as lead-boron silicate glass (PbO-SiO2-B2O3-Al2O3) The glass frit contains lead borosilicate glass. The reason why is used is that it has good wettability with ruthenium oxides and its thermal expansion coefficient is based on This is because it has a thermal expansion coefficient close to that of the plate and is suitable in terms of viscosity during firing.

[0006] In order to improve the characteristics of the thick film resistors after film formation, For example, they contain additives to adjust the temperature coefficient of resistance (TCR) and improve current noise. The traditional additives used to reduce noise include titanium dioxide (TiO2). In JP-A-61-206201, The conductive powder, the glass powder containing PbO, and the titanium oxide are mixed in an amount of 100% by weight of the solid content in the composition. A thick-film resistor composition containing 0.025 to 6.0 parts by weight of Ti per part. In addition, Japanese Patent Publication No. 63-035081 discloses a method for producing a fluorine-containing oxide using RuO2 and PbO. The glass containing the niobium oxide and the finely divided inorganic powder of Nb2O5 are dispersed in an inert liquid vehicle. A thick-film resistor composition comprising: a thick-film resistor having an additive amount of Nb2O5 of 0.1% by weight to 0.8% by weight; has been disclosed.

[0007] The glass powder constituting these compositions for thick film resistors contains lead. The use of thick film resistor paste containing such harmful lead is undesirable from an environmental standpoint. Therefore, in recent years, there has been a strong demand for practical use of lead-free paste for thick film resistors. Therefore, research and development of lead-free paste for thick film resistors is currently underway. Proposal of lead-free glass frit for thick-film resistor composition used in paste for A proposal has been made. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 61-206201 [Patent Document 2] Special Publication No. 63-035081 Summary of the Invention [Problem to be solved by the invention]

[0009] In a composition for a thick film resistor containing titanium oxide or niobium oxide as an additive, Titanium oxide or niobium oxide is added as a powder to the thick film resistor composition or Alternatively, it is added in advance to the glass powder constituting the thick film resistor composition. Using titanium oxide or niobium oxide as an additive, we have developed a thick-film resistor that does not contain lead. When the resistance value is increased to 10 kΩ or more, the current noise becomes large. There is a problem.

[0010] The object of the present invention is to provide a thick-film resistor that is substantially free of lead and has a high resistance. Moreover, it is possible to form a resistor having good electrical characteristics with small current noise. To provide a composition for a thick-film resistor, and to provide a thick-film resistor using the composition for a thick-film resistor. The present invention aims to provide an antibody paste and a thick film resistor. [Means for solving the problem]

[0011] The thick-film resistor composition of the present invention comprises a conductive powder and a glass frit that is substantially free of lead. and contains 3.0 mass% to 15.0 mass% steatite. The amount of steatite added is 5.0% by mass or more and 14.0% by mass or less. is preferred.

[0012] The content of the conductive powder is preferably 5% by mass or more and 30% by mass or less. The conductive powder is preferably made of a ruthenium compound. Preferably, the ruthenium dioxide and / or alkaline earth metal ruthenate are used. stomach.

[0013] The paste for a thick film resistor of the present invention contains a composition for a thick film resistor and an organic vehicle, The present invention is characterized in that the composition for thick-film resistors of the present invention is used as the composition for thick-film resistors. do.

[0014] The content of the organic vehicle is 30% by mass based on the mass of the paste for thick film resistors. It is preferably from 1 to 50% by mass.

[0015] The thick-film resistor of the present invention is made of a sintered body containing a conductive component, a glass component, and steatite. The glass component is substantially free of lead, and the total mass of the conductive component and the glass component is The sintered body is characterized in that it contains 3.0 mass% or more and 15.0 mass% or less of steatite. The content of steatite is preferably 5.0% by mass or more and 14.0% by mass or less. The content of the conductive component is preferably 5% by mass or more and 30% by mass or less. The conductive component preferably comprises a ruthenium compound. The ruthenium compound is It is preferably made of ruthenium dioxide and / or alkaline earth metal ruthenate. . Effect of the Invention

[0016] The thick-film resistor composition, thick-film resistor paste, and thick-film resistor of the present invention are free of harmful lead. It has excellent electrical properties, including high resistance and low current noise, without containing any fluorine. This allows it to exhibit excellent properties, and by replacing conventional thick film resistor pastes that contain lead, Because we can provide resistive components such as chip resistors and hybrid ICs that are free from environmental pollution issues , and its industrial value is extremely great. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The thick-film resistor composition, thick-film resistor paste, and thick-film resistor of the present invention will be described below. , will be explained in detail.

[0018] (1) Composition for thick film resistors The thick-film resistor composition of the present invention comprises a conductive powder, a glass frit, and steatite. It is characterized in that it contains, as a main component.

[0019] [Conductive powder] The conductive powder constituting the composition for thick film resistor of the present invention is a ruthenium compound. The ruthenium compound is preferably ruthenium dioxide (RuO2), ruthenium oxide (RuO2), or ruthenium oxide (RuO2). Alkaline earth metals, i.e. calcium ruthenate (CaRuO3), sulphur ruthenate Strontium (SrRuO3), and barium ruthenate (BaRuO3) are examples. The thick-film resistor composition of the present invention contains a ruthenium compound selected from the above. It is preferable that the conductive powder contains at least one of the following materials: It can be obtained.

[0020] Calcium ruthenate, strontium ruthenate, or barium ruthenate The material is made of ruthenium dioxide powder and hydroxides of calcium, strontium, or barium. It is obtained by a dry method in which the material is mechanically mixed with oxides or carbonates, heat-treated, and then pulverized. In order to obtain these powders with small and uniform particle size, it is necessary to add them to an alkaline solution. Ruthenium chloride and calcium chloride, strontium chloride, or barium chloride The precipitate is washed and dried, and then heated at about 600° C. or higher for 9 hours. A roasting process at a temperature below 00°C is used.

[0021] The average particle size of the conductive powder as measured by the BET method is preferably 1.0 μm or less, and more preferably 0. It is more preferable that the thickness is 2 μm or less. This makes it possible to obtain a thick-film resistor by firing. This allows the conductive path to be finer, and the variation in resistance value and the magnitude of current noise are appropriately suppressed. It becomes possible to do so.

[0022] In the composition for thick-film resistor of the present invention, the content of the conductive powder is Depending on the desired resistance value, the type and particle size of the conductive powder and glass frit, For example, to obtain a resistor with a sheet resistance of 5 kΩ or more, the The content of the conductive powder is 5% by mass or more and 30% by mass or less.

[0023] [Glass frit] The glass frit constituting the thick film resistor composition of the present invention is substantially free of lead. It is characterized by:

[0024] Here, "substantially free of lead" means that the lead content in the glass frit is within the limits of RoH The lead content is below the S Directive regulation value (0.1 mass%) or is measured using normal measuring equipment. This means that the concentration is below the detection limit.

[0025] Other glass components in the glass frit constituting the thick film resistor composition of the present invention Basically, there is no limitation on the glass frit. Potassium earth zinc glass (SiO2-B2O3-RO-ZnO-Al2O3: R is Ca, Sr , and Ba), borosilicate glass (SiO2-B2O3 ), aluminoborosilicate glass (SiO2-B2O3-Al2O3), or borosilicate Alkaline earth oxide glass (SiO2-B2O3-RO: R is selected from Ca, Sr, and Ba) At least one selected from the above can be preferably used.

[0026] The average particle size of the glass frit constituting the composition for thick film resistor of the present invention is determined by a laser diffraction particle size determination method. In terms of D50 (median diameter) measured by the degree of grain distribution, it is preferable that the diameter is 5 μm or less. It is more preferable that the particle size of the glass frit is in the range of 1 μm to 3 μm. By doing so, the conductive path in the thick film resistor can be made fine, and the resistance value of the thick film resistor can be reduced. It is possible to suppress the variation and current noise. To obtain the glass frit, the glass frit is melted and cooled, and then milled in a known mill such as a ball mill or a jet mill. The powder may be pulverized by the method described above.

[0027] In the glass frit constituting the thick film resistor composition of the present invention, the softening point of the glass is The temperature is preferably in the range of 550°C to 750°C, and more preferably in the range of 600°C to 700°C. It is more preferable that the softening point of the glass is in the range of 550°C. When the paste was baked to form the resistor, the glass frit melted too much, causing the resistor pattern to crack. If the softening point of the glass is higher than 750°C, the glass frit may melt and This makes it difficult to apply the conductive powder and reduces the current of the resulting thick film resistor. Noise increases.

[0028] Here, the softening point is determined by measuring the softening point of glass in air at a rate of 5°C / min to 20°C / min using a differential thermal analysis method. The temperature is raised and heated at a temperature higher than the temperature at which the lowest differential heat curve decreases. It is the temperature at which the next differential heat curve on the higher temperature side shows a peak decrease.

[0029] In the glass frit constituting the composition for a thick film resistor of the present invention, the thermal expansion coefficient of glass is 40 x 10 -7 / K or more 100×10 -7 / K or less, and 0×10 -7 / K or more 90×10 -7 It is more preferable that the range is 0.1 to 1.0. For example, when an alumina substrate is used, a glass substrate made of glass having a thermal expansion coefficient in this range is used. By using a lithography, the thermal expansion coefficient of the obtained thick film resistor is made smaller than that of the alumina substrate. The thermal expansion coefficient of the glass frit is close to that of the glass melt, so there is no problem with tensile stress. It can be molded into a bar and measured with a thermomechanical analyzer (TMA).

[0030] The softening point and thermal expansion coefficient of the above glass frit depend on the composition of the glass frit. It is possible to control this by considering the composition of the

[0031] The content of glass frit in the composition for thick film resistors also affects the thickness of the resulting thick film resistors. Depending on the desired resistance value in the For example, to obtain a resistor with a sheet resistance of 5 kΩ or more, the Generally, the glass frit content is 70% by weight or more and 95% by weight or less depending on the conductive powder content. % or less.

[0032] [Steatite] The composition for a thick film resistor of the present invention is characterized by containing steatite. is expressed by the formula MgO·SiO2. Steatite has excellent insulation properties even in high temperature environments. It also exhibits excellent mechanical strength and oxidation resistance. Therefore, it has been conventionally used as a high-frequency insulator or an insulating terminal for communication devices. Steatite also has a large thermal expansion coefficient of 77 x 10 -7 / K.

[0033] The addition of steatite increases the resistance value of thick film resistors and reduces current noise. Steatite has the function of reducing the conductive particles that gather between the glass particles. It works to reduce the aggregation caused by the melting and flow of glass during the firing process. Theatite easily wets glass, and its large thermal expansion coefficient enhances this effect. It is thought that.

[0034] The BET average particle size of the steatite powder constituting the composition for thick film resistor of the present invention is 2 μm. It is preferable that the thickness is 1 μm or less, and more preferable that the thickness is 1 μm or less.

[0035] The content of steatite in the composition for thick film resistor is 3.0 mass% or more and 15.0 mass% or less. The content of steatite is preferably 5.0 mass % or more and 14.0 mass % or less. If the content is 3.0 mass % or more, the effect of reducing current noise is sufficiently exhibited. In addition, if the steatite content is 15.0 mass% or less, the resistance value can be increased. This allows current noise to be reduced without exceeding the limit.

[0036] [Optional ingredients] In the thick-film resistor composition of the present invention, the conductive powder, the glass frit and the steatite are In addition, other additives can be added. For example, in the case of a thick film resistor, Adjustment of electrical properties such as resistance value and temperature coefficient of resistance, adjustment of expansion coefficient, improvement of voltage resistance, For the purpose of other modifications, the thick film resistor composition of the present invention may contain manganese dioxide, copper oxide, pentaoxide, It is possible to appropriately contain inorganic components such as niobium oxide, tin oxide, tantalum oxide, and titanium oxide. can.

[0037] The content of these inorganic components is 0. It is common for the content to be in the range of 0.5% by mass or more and 10% by mass or less.

[0038] (2) Thick film resistor paste The thick-film resistor paste of the present invention contains a thick-film resistor composition and an organic vehicle. It is particularly preferable that the thick-film resistor composition of the present invention is used as the film resistor composition. Specifically, the thick-film resistor paste of the present invention comprises the thick-film resistor composition of the present invention. The details are described below.

[0039] [Organic vehicle] The organic vehicle constituting the paste for thick film resistors is composed of at least a resin and a solvent. can be.

[0040] Resins that can be used as the organic vehicle include ethyl cellulose resin, butyrate resin, Examples of the resins include vinyl acrylate resin (polyvinyl butyral), acrylic resin, etc. A resin that decomposes at a temperature before the glass softens is preferred. More preferably, the temperature is 500° C. or lower. Resins which decompose with temperature are preferred.

[0041] Solvents that dissolve resins include terpineol, butyl carbitol, and butyl carbitol. For example, ethyl acetate or the like can be used.

[0042] The blending ratio of the resin and the solvent in the organic vehicle prepared by using these resins and solvents is set to a desired value. This can be adjusted appropriately depending on the viscosity and application.

[0043] In addition, taking into consideration the continuous printability required for thick film resistor paste, the drying speed of the paste was From the viewpoint of control, a plasticizer having a high boiling point can be further added. The blending ratio of the plasticizer can also be appropriately adjusted depending on the desired drying speed.

[0044] The ratio of the organic vehicle to the paste for the thick film resistor is not particularly limited. Generally, the amount is between 30% and 50% by mass based on the mass of the paste for film resistors. It is.

[0045] [Other ingredients] The paste for thick-film resistors of the present invention contains, in addition to the composition for thick-film resistors and the organic vehicle, additives. For example, the conductive powder and other inorganic components may be prevented from agglomerating. From the viewpoint of coating workability, the rheology control agent may be added. It may contain a chlorine atomizing agent.

[0046] [Preparation method of paste for thick film resistor] The paste for the thick film resistor may be prepared by using a known technique. For example, a three-roll mill may be used. A mill, a ball mill, etc. can be used.

[0047] The paste for thick film resistors contains conductive powder, glass frit, steatite, and It is desirable to disaggregate the inorganic components such as those mentioned above and disperse them in the organic vehicle. .

[0048] (3) Thick film resistor The thick-film resistor of the present invention is made of a sintered body containing a conductive component, a glass component, and steatite. The conductive component is a ruthenium compound, i.e., ruthenium dioxide, calcium ruthenate, A small amount selected from the group consisting of ruthenium, strontium ruthenate, and barium ruthenate. The glass component is characterized by being substantially free of lead. That is, the thick film resistor of the present invention is formed by using the thick film resistor paste of the present invention. The thick film resistor is formed of a sintered body containing the composition for a thick film resistor.

[0049] Therefore, the conductive component is the same as the conductive powder constituting the thick film resistor composition of the present invention. The glass component is the glass frit constituting the thick film resistor composition of the present invention. The content of steatite is also the same as that of the thick-film resistor composition of the present invention. As in the case of the above, the conductive component and the glass component are 3.0 mass% or more and 15.0 mass% or more of the total mass of the conductive component and the glass component. 0.0 mass% or less, preferably 5.0 mass% or more and 14.0 mass% or less. The description of the conductive component, the glass component, and the steatite is omitted here.

[0050] The manufacturing method of the thick film resistor will be described below. The ratio of the conductive powder and the glass frit in the antibody can be appropriately adjusted.

[0051] [Manufacturing method of thick film resistors] The method for producing the thick film resistor of the present invention is not limited to the following, and the processing conditions, etc. The above can be appropriately changed using known means and methods.

[0052] First, a coating process is performed in which a paste for thick film resistors is applied to a substrate. Electrodes made of silver (Ag), palladium (Pd), etc. are formed on the ceramic substrate, The paste for thick film resistors of the present invention is applied thereon by means of screen printing or the like. .

[0053] Next, a firing step is performed to fire the substrate on which the thick-film resistor paste is applied, thereby forming a thick-film resistor. Specifically, in the coating process, the paste for thick film resistors applied to the substrate is The coated substrate is dried in an oven or the like, and then sintered in a belt furnace or the like to form a conductive layer. The paste for thick-film resistors is basically made of a sintered body containing a glass component and a sintered body containing a glass component. The components other than those originating from the conductive powder and glass frit, i.e., organic The resins and solvents that make up the shell, as well as other organic additives, are all removed through the baking process. The whole is broken down into parts.

[0054] Through the steps described above, the thick film resistor of the present invention is obtained.

[0055] According to the thick-film resistor of the present invention, ruthenium dioxide, calcium ruthenate, ruthenium At least one selected from strontium ruthenate and barium ruthenate The conductive component is composed of at least a glass component substantially free of lead, and steatite. Therefore, it does not contain lead, has high resistance, small current noise, and good electrical properties. A thick film resistor having excellent characteristics is provided.

[0056] The thick-film resistor of the present invention contains, in addition to the conductive component and the glass component, manganese dioxide, copper oxide, It can contain inorganic components such as niobium pentoxide, tin oxide, tantalum oxide, and titanium oxide. .

[0057] In the above, the present invention has been described mainly using specific embodiments. The best configuration and method for carrying out the present invention have been disclosed. However, the present invention is not limited to the above. The shape, material, quantity, and other detailed configurations of the above-described embodiments are not to be construed as limiting the present invention. It is possible for a person skilled in the art to make omissions, additions, changes or modifications. However, such a method is still within the scope of the present invention. EXAMPLES

[0058] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to the following examples.

[0059] Example 1 [Preparation of composition for thick film resistor] [Conductive powder] Ruthenium dioxide (RuO2) was used as the conductive powder. Ruthenium dioxide has the following properties: Ruthenium hydroxide was prepared by roasting in air at 800°C for 2 hours. The average particle size was 0.05 μm.

[0060] [Glass frit] Glass frit: 10% by mass SrO-4, 3% by mass SiO2-16% by mass B2O3 -4 mass% Al2O3-20 mass% ZnO-7 mass% Na2O glass frit The glass frit was prepared by the usual means of mixing, melting, quenching, and grinding. In the crushing process, the glass frit was crushed into its particles. Grind until the diameter reaches 1.5μm (D50, median diameter, measured by laser diffraction particle size distribution measurement) did.

[0061] [Steatite] Steatite was replaced with Forsterite (product name: FF-200-M) manufactured by Marusu Glaze LLC. 40, average particle size 2.5μm) was mixed with molten SiO2 powder, and the mixture was roasted at 1100℃. The resulting roasted material was crushed to obtain the BE of steatite. The average particle size was set to 1.0 μm.

[0062] [Organic vehicle] As the organic vehicle, a solution of ethyl cellulose in terpineol was used. The mixing ratio of ethyl cellulose:terpineol was 1:9.

[0063] [Preparation of paste for thick film resistors] The target thickness of the thick film resistor after firing is 7μm to 9μm, and the sheet resistance is 10kΩ (± 20%), 33kΩ (±20%), and 100kΩ (±20%). As Comparative Examples 1 to 3, the above-mentioned conductive powder, glass frit, and steatite were used. Thick film resistors containing 17.5 mass%, 77.5 mass%, and 5.0 mass% of 60% by mass of the composition for use and 40% by mass of the organic vehicle were mixed and kneaded in a three-roll mill. A resistive paste for a thick-film resistor was prepared. The composition of the thick-film resistor composition is shown in Table 1.

[0064] [Making thick film resistors] The above-mentioned electrode was formed on an alumina substrate using AgPd paste. The paste for thick film resistors was applied to a 1mm wide plate with a 1mm gap between electrodes (1mm x 1mm ) by screen printing, and then the thick film resistor The paste was dried in an oven at 150°C for 10 minutes, and then calcined in a belt furnace. The firing was performed under the conditions of a peak temperature of 850°C, a peak time of 9 minutes, and a total firing time of 30 minutes. A thick film resistor was fabricated by forming a thin film resistor.

[0065] [Thick film resistor evaluation] In order to evaluate the electrical characteristics of the thick film resistors, the following tests were performed on each thick film resistor. , sheet resistance, and current noise were measured.

[0066] [Sheet resistance value] The sheet resistance of the thick film resistor was measured using a multimeter (KEITHLEY Model 200 1) was used and measurements were taken using the four-terminal method.

[0067] [Current noise] Current noise was measured using a noise meter (Quan-Tech, Model 315C). The measurements were taken with an applied power of 1 / 10 W.

[0068] Table 2 shows the measurement results of the sheet resistance and current noise.

[0069] Example 2 Ruthenium dioxide, glass frit, and steatite, 17.2% by weight, 73. 0% by mass and 9.8% by mass of the thick film resistor composition were used. A thick-film resistor was obtained in the same manner as in Example 1 and was evaluated.

[0070] Example 3 Ruthenium dioxide, glass frit, and steatite were added at 17.4% by weight, 68. Other than the use of compositions for thick film resistors containing 6.0% by mass and 14.0% by mass A thick-film resistor was obtained in the same manner as in Example 1 and was evaluated.

[0071] Comparative Example 1 No steatite was added, and ruthenium dioxide and glass frit were added at 15.0 mass%. Except for using a thick film resistor composition containing 85.0 mass % of In the same manner as in 1, a thick-film resistor was obtained and evaluated.

[0072] Comparative Example 2 No steatite was added, and ruthenium dioxide and glass frit were added at 10.0 mass%. Except for using a thick film resistor composition containing 90.0 mass % of In the same manner as in 1, a thick-film resistor was obtained and evaluated.

[0073] Comparative Example 3 No steatite was added, and ruthenium dioxide and glass frit were added at 7.5 mass% and The same procedure as in Example 1 was repeated except that a thick-film resistor composition containing 92.5% by mass of In the same manner as described above, a thick film resistor was obtained and evaluated.

[0074] Comparative Example 4 Ruthenium dioxide, glass frit, and steatite were added at 17.5% by weight, 80. The thick-film resistor composition was used in a ratio of 0 mass % and 2.5 mass %. A thick-film resistor was obtained in the same manner as in Example 1 and was evaluated.

[0075] Comparative Example 5 Ruthenium dioxide, glass frit, and steatite were added at 17.5% by weight, 65. 0% by mass and 17.5% by mass of thick-film resistor composition were used. A thick-film resistor was obtained in the same manner as in Example 1 and was evaluated.

[0076] [Table 1]

[0077] [Table 2]

[0078] [Consideration] From the electrical characteristics of the thick-film resistors produced in the examples and comparative examples of the present invention, it was found that the additive The thick-film resistors using atite (Examples 1 to 3) were similar to the thick-film resistors not containing additives (Comparative Example 1 to 3) and thick-film resistors in which the amount of steatite added is outside the range of the present invention (Comparative Examples 4 and In comparison with 5), the current noise is sufficiently small according to the desired sheet resistance value. It is therefore understood that this is an excellent thick film resistor.

Claims

1. A composition for thick-film resistors, comprising a conductive powder consisting of ruthenium dioxide and / or alkaline earth metal ruthenate, and a glass frit that is substantially free of lead, and characterized in that 3.0 mass % or more and 15.0 mass % or less of steatite is added.

2. A composition for thick film resistors as described in claim 1, wherein the amount of steatite added is 5.0 mass % or more and 14.0 mass % or less.

3. A composition for thick film resistors as described in claim 1, wherein the content of the conductive powder is 5 mass% or more and 30 mass% or less.

4. A paste for thick film resistors comprising a composition for thick film resistors and an organic vehicle, wherein the composition for thick film resistors is a composition for thick film resistors described in any one of claims 1 to 3.

5. The content of the organic vehicle is 30 mass% based on the mass of the paste for thick film resistors. The paste for a thick film resistor according to claim 4 , wherein the content of the cation exchange resin is from 0.01 to 0.5% by mass.

6. A thick-film resistor comprising a sintered body containing a conductive component consisting of ruthenium dioxide and / or alkaline earth metal ruthenate, a glass component, and steatite, wherein the glass component is substantially free of lead and contains 3.0 mass% or more and 15.0 mass% or less of steatite relative to the total mass of the conductive component and the glass component.

7. A thick film resistor as described in claim 6, wherein the steatite content is 5.0 mass % or more and 14.0 mass % or less.

8. A thick film resistor as described in claim 6 or 7, wherein the content of the conductive component is 5 mass % or more and 30 mass % or less.

Citation Information

Patent Citations

  • Resistand composition and method of producing same

    JP1982084101A

  • Thick film resistor composition

    JP1986206201A

  • Light quantity correcting device for video camera

    JP1988035081A

  • Thick film resistor

    JP1992320003A

  • Cermet resistors, their composition and method of manufacture

    US3416960A